Global Research Alliance N2O chamber methodology guidelines: Summary of modeling approaches. Issue 5 (27th August 2020) - Giltrap, Donna; Yeluripati, Jagadeesh; Smith, Pete; Fitton, Nuala; Smith, Ward; Grant, Brian; Dorich, Christopher D.; Deng, Jia; Topp, Cairistiona FE; Abdalla, Mohamed; Liáng, Lìyǐn L.; Snow, Val
Abstract: Measurements of nitrous oxide (N2 O) emissions from agriculture are essential for understanding the complex soil–crop–climate processes, but there are practical and economic limits to the spatial and temporal extent over which measurements can be made. Therefore, N2 O models have an important role to play. As models are comparatively cheap to run, they can be used to extrapolate field measurements to regional or national scales, to simulate emissions over long time periods, or to run scenarios to compare mitigation practices. Process‐based models can also be used as an aid to understanding the underlying processes, as they can simulate feedbacks and interactions that can be difficult to distinguish in the field. However, when applying models, it is important to understand the conceptual process differences in models, how conceptual understanding changed over time in various models, and the model requirements and limitations to ensure that the model is well suited to the purpose of the investigation and the type of system being simulated. The aim of this paper is to give the reader a high‐level overview of some of the important issues that should be considered when modeling. This includes conceptual understanding of widely used models, common modeling techniques such as calibration and validation, assessing model fit, sensitivity analysis, and uncertainty assessment. We also review examples of N2 O modeling for different purposes and describe three commonly used process‐based N2 O models (APSIM, DayCent, and DNDC).